2017
DOI: 10.1111/ppe.12408
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vaccination Against Human Papillomavirus on Fecundability

Abstract: Background The human papillomavirus (HPV) vaccine was developed to prevent infection with strains of HPV that cause cervical cancer. While HPV infection has been associated with reduced semen quality and lower pregnancy rates in some, no studies have examined the relationship between HPV vaccination and fecundability. We hypothesize that HPV prevention via vaccination will protect fecundity. Methods We analyzed data from Pregnancy Study Online (PRESTO), a preconception cohort of North American pregnancy plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Studies have reported that women with gynecological diseases were prone to HR-HPV infection, due to unstable sexual hormone levels, poor function of the immune system, lower resistance to HR-HPV, and weakviral clearance. 33,34 Our findings indicated that HPV16 is the most frequently identified type in women with ASC-US, LSIL, and HSIL+ in Shanxi, confirming that HPV16 is the main HR-HPV type associated with cervical lesions.…”
Section: Discussionsupporting
confidence: 61%
“…Studies have reported that women with gynecological diseases were prone to HR-HPV infection, due to unstable sexual hormone levels, poor function of the immune system, lower resistance to HR-HPV, and weakviral clearance. 33,34 Our findings indicated that HPV16 is the most frequently identified type in women with ASC-US, LSIL, and HSIL+ in Shanxi, confirming that HPV16 is the main HR-HPV type associated with cervical lesions.…”
Section: Discussionsupporting
confidence: 61%
“…Response. The HPV infection is linked to significant reproductive function abnormalities in women (Souho et al, 2015) and in men (McInerney et al, 2017). One study reported that women who were found to be HPV-positive were six times less likely to become pregnant after intrauterine insemination (Ambühl et al, 2016).…”
Section: Findings -The Most Common Hpv Vaccine Questionsmentioning
confidence: 99%
“…Similarly, another study on women who were found to have a current cervical HPV infection experienced a decline in conception when using in vitro fertilization (Garolla et al, 2018). The HPV infection also negatively affects fertility in men as it can reduce sperm motility and increase antisperm antibodies (McInerney et al, 2017). On the contrary, the HPV vaccine has no adverse effect on oocyte counts and fertilization rates (Demir et al, 2020).…”
Section: Findings - the Most Common Hpv Vaccine Questionsmentioning
confidence: 99%
“…[19][20][21] In the sole study of HPV vaccination and fecundability, a history of HPV vaccination had little effect on fecundability overall, but vaccination was associated with higher fecundability among women with a history of sexually transmitted infections (STIs). 22 Treatment for suspected CIN involves several steps. First, a colposcopy is performed to visually examine the cervix, vagina, and vulva.…”
mentioning
confidence: 99%
“…The volume of tissue removed is generally greatest for conization (a procedure usually reserved for severe precancerous lesions), 23 followed by LEEP or laser cone, followed by ablative procedures (laser ablation or cryotherapy). 22 Some women with persistent or recurrent CIN2/3 may require repeat procedures, resulting in the loss of additional cervical length. Although regeneration of the cervical tissue is possible, the more tissue that is removed, the lower the likelihood of regeneration.…”
mentioning
confidence: 99%